The great Gatsby [large type] - Fitzgerald, F. Scott (Francis Scott), 1896-1940 (Thorndike Press, a part of Gale, a Cengage Company, 2021)
"In a single, engaging volume, The Great Gatsby presents a helpful literary guide to one of America's most prized classic novels. First published in 1925, F. Scott Fitzgerald's The Great Gatsby captured the spirit of the Jazz Age and examined the American obsession with love, wealth, material objects, and class. Considered one of the great novels of the 20th century, Fitzgerald s famous work remains relevant for its observations on the pursuit of the American dream"--